2008
DOI: 10.1080/10862960802502162
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Text Processing: A Comparison of Four Methods

Abstract: Tests commonly used to determine progress in reading skill and proficiency typically assess reading products (e.g., identifying characters or factual information, sequencing events) rather than the reading processes used to generate responses (e.g., hypothesizing, evaluating, monitoring, questioning). Yet, effective processing often determines how successfully a reader responds on testing measures. Identifying measures that can assist educators to better understand how a student processes text is vital. The pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…However, Beck and Kucan (1997) and thoughts (Scott, 2008). In this way, text processing and learning activities are directly revealed without delay and are expressed in students' own words.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, Beck and Kucan (1997) and thoughts (Scott, 2008). In this way, text processing and learning activities are directly revealed without delay and are expressed in students' own words.…”
Section: Introductionmentioning
confidence: 98%
“…Significant research has focused on explicit efforts to understand the thinking process and the comprehension of text (Davey, 1983; Bereiter and Bird, 1985). Utilizing think-alouds in such a manner involves teacher modeling, teacher-student interaction, and finally, the independent use by the student.However, Beck and Kucan (1997) and thoughts (Scott, 2008). In this way, text processing and learning activities are directly revealed without delay and are expressed in students' own words.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In order to reveal the full spectrum of a system's strong and weak points, one needs to evaluate it using multiple methods (Ebling & John, 2000;Peleg, Shackak, Wang, & Karnieli, 2009;Scott, 2008;Zabed Ahmed, 2008). However, the sets of issues the different methods elicit may overlap and, as a result, the added value of applying an extra method may be limited.…”
Section: Comparisons Of Methodsmentioning
confidence: 99%
“…Other comparisons have addressed the differences between thinking-aloud, questionnaires and/or interviews when applied to tasks or systems without personalized features. In the case of text-processing, Scott (2008) found that thinking-aloud and interviews elicit the same responses. Meanwhile, other researchers did find differences between the methods.…”
Section: Comparisons Of Methodsmentioning
confidence: 99%